2020
DOI: 10.1186/s12882-020-02063-6
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-burden in people living with frailty and chronic kidney disease

Abstract: Background Frailty is independently associated with worse health-related quality of life (HRQOL) in chronic kidney disease (CKD). However, the relationship between frailty and symptom experience is not well described in people living with CKD. This study’s aim was to evaluate the relationship between frailty and symptom-burden in CKD. Methods This study is a secondary analysis of a cross-sectional observational study, the QCKD study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 49 publications
0
21
0
3
Order By: Relevance
“…In addition, the current review reported a higher level of informal caregiver burden in caregivers who had to assist patients with personal care needs and those patients on dialysis who suffered other chronic diseases. Ageing, frailty, and multi-morbidity are highly prevalent in ESKD [ 57 , 58 ] placing significant burdens on informal caregivers highlighting the urgent need for the development of supportive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the current review reported a higher level of informal caregiver burden in caregivers who had to assist patients with personal care needs and those patients on dialysis who suffered other chronic diseases. Ageing, frailty, and multi-morbidity are highly prevalent in ESKD [ 57 , 58 ] placing significant burdens on informal caregivers highlighting the urgent need for the development of supportive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A more realistic sample size of 268 and 200 participants would be needed if using the SPPB or POS-S Renal, respectively. Physical function and symptom-burden are clinical outcomes relevant and important for people living with CKD and people living with frailty alike [14,15,[53][54][55]. Therefore, we suggest that either may be used as the primary outcome measure of interest in a RCT investigating the effectiveness of a home-based exercise programme in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…• Kidney Symptom Questionnaire (KSQ): The KSQ assesses the frequency, intrusiveness, and total impact of a range of 13 common kidney disease-related symptoms. This questionnaire has been validated by our group 27 and used widely in the literature 28 .…”
Section: Secondary Outcomesmentioning
confidence: 99%